Performance-based Seismic Design Using REDSET: A Novel Reliability Evaluation Approach - J. Ramon Gaxiola-Camacho; Achintya Haldar; Aaron Gutierrez-Lopez (Science and Technology: Developments and Applications Vol. 3, 2025)
Considering the economic impacts of recent major earthquakes all over the world, the Performance-Based Seismic Design (PBSD) concept is now under development, replacing the life safety concept, to be incorporated in the next generation of design guidelines. Although PBSD is a risk-based concept, no such acceptable concept is currently available. To fill this knowledge gap, the authors and their team recently proposed a concept known as the Reliability Evaluation of Dynamic Systems Excited in the Time Domain (REDSET). The implementation of PBSD using REDSET is demonstrated in this chapter. The structures are represented by finite elements and the seismic loading is applied in the time domain incorporating all major sources of nonlinearity and uncertainty in the design variables. The Limit Performance Functions (LPFs) are implicit for this class of problems. To retain simplicity, they are made explicit using the response surface concept and the First-Order Reliability Method (FORM) is used to extract the reliability evaluation. The basic Monte Carlo Simulation (MCS) method is used to verify REDSET. The authors then developed required serviceability LPFs correlating them with performance levels of Collapse Prevention (CP), Life Safety (LS), and Immediate Occupancy (IO), as suggested in PBSD. The capabilities of REDSET to implement PBSD are demonstrated with the help of examples. Uncertainties in the design earthquake time history are incorporated using multiple time histories as suggested in design guidelines. The information on the reliability estimated using REDSET correlates well with different levels of performance. The study clearly indicates that reliable information can be obtained using only a few hundred instead of millions of deterministic nonlinear finite element analyses. The authors believe that REDSET can be used to advance the development of the PBSD philosophy further.